Cancer immunotherapy: potential involvement of mediators - S. Ben-Efraim (Mediators of Inflammation)
The description of a cell-free soluble anti-tumour factor by Carswell et al. in 1975 (Proc Natl Acad Sci USA, 72: 3666–3670) was followed by a long series of experimental and clinical investigations into the role of cell-free mediators in cancer immunotherapy. These investigations included research on the effects of macrophage–derived eicosanoids (cycloxygenase and lipoxygenase derivates of arachidonic acid) and of monokines such as tumour necrosis factor-α, interleukin-1 and granulocyte–monocyte–macrophage–colony stimulating factor) and of lymphocyte products: interleukins and interferons. The investigations yielded information on the effects of various factors on macrophage and T-cell activation in vitro, determination of direct anti-tumour properties on animal and human tumour cells in vitro and on therapeutic effectiveness in tumour-bearing individuals either alone or in combination with other therapeutic factors and their production by tumour cells. During recent years much effort has been dedicated towards the use of the tumour cells transfected with cytokine genes in the preparation of cancer vaccines. Cycloxygenase products (prostaglandins) were usually assumed to inhibit expression of anti-tumour activity by macrophages and an increase in their production in cancer patients was considered as a poor prognostic index. Lipoxygenase (leukotrienes) products were assumed to exhibit antitumour activity and to induce production of IL-1 by macrophages. Interleukins 2, 4, 6, 7, 12 and the interferons were extensively tested for their therapeutic effectiveness in experimental tumour models and in cancer clinical trials. The general conclusion on the use of cell-free mediators for cancer immunotherapy is that much still has to be done in order to assure effective and reproducible therapeutic effectiveness for routine use in the treatment of human neoplasia.